Taking Sides: The Frames of Online Media on the Bilateral Relationship Between Indonesia and Malaysia - WIDODO, GATUT PRIYO; INDRAYANI, INRI (Jurnal Studi Pemerintahan, 2014)
The relations between Indonesia and Malaysia arealways full of dynamics. Indonesia is always knownas old brother of Malaysia since it has similar history,religion also socio cultural background. Somedecades show that the decline of relationship of bothcountries. Another time, as ASEAN members, thetwo countries devote their nationalities to purify theircollective identities as Eastern nations. The objectiveof the research is to extricate the construction ofKompas online and Utusan online toward news coverageof the borders dispute between Indonesia-Malaysia in 2010. This research is proposed to examinecentral issues which reported by Kompas onlineand Utusan online consistently. As a media, Kompascoverage dominates circulation nationally.Kompas.com was the pioneer of online news in Indonesiaand was born in reformation era. Utusan isa prominent media industry in Malaysia that wasconducted by UMNO as the ruling party in Malaysiafor some periods. The method used in this researchis framing method by Robert N. Entman’swhich consists of four steps identification: definingproblem, diagnosing causes, moral judgment anda treatment recommendation. This research foundthat Kompas news covered the border dispute mustbe negotiated as recognition of Indonesia dignity.On the contrary, Utusan’s spectacle focused on theIndonesian demonstrators anarchism during the dispute.Keywords: Online Media, media construction, theborder dispute, Indonesia-Malaysia’s Bilateral Relations